APPLICATION OF NEWSROOM CONVERGENCE IN REGIONAL MEDIA SOLOPOS NEWSROOM - Ruth Elisha Wijayanti Putri (Jurnal Komunikasi dan Media, 2022)
Changes in the consumption pattern of public information media ultimately have an impact on the dimming of the existence of the print media industry. The dynamics of technological change and competition are also felt by regional print media with a smaller market scale. Convergence is an alternative solution for regional print media to adapt to changes that occur, one of which is Solopos. In practice, the application of convergence in Solopos results in a reorganization of media management and newsroom processing. Thus directing the media to the concept of newsroom. This study aims to describe the application of newsroom convergence in the Solopos regional media newsroom. Descriptive qualitative research method was carried out by means of semi-structured interviews, observation, and documentation studies for data collection. Informants in this research included managing editors, print content managers, online content managers, Solopos reporter. Through this research, it has been found that convergence newsroom in the Solopos newsroom is carried out by implementing online-first, developing Content Management System (CMS) Solopos as a news control center, integrating the role of journalists between platforms in journalistic workflows and unifying the placement of newsrooms between platforms into a single newsroom. This research concludes that the editors in Solopos are currently implementing convergence with the newsroom 2.0: cross media newsroom since the beginning of 2022 to the journalistic workflow and editorial management system. The maximum unification of the roles and duties of journalists between platforms only occurs at the content gathering stage and is not yet fully controlled centrally.